The Affiliation to the Health System among Venezuelan Migrants in Colombia - Rodríguez Vargas, Juan Manuel; Vargas-Valle, Eunice Danitza; López Jaramillo, Ana María (Población y Salud en Mesoamérica, 2020)
Introduction: Venezuelan migrants’ access to the health system is fundamental to their survival and future well-being. This article aims to analyze the level of affiliation to the health care system of these migrants in the urban areas in Colombia by arrival periods and the associated sociodemographic and labor factors. Methodology: To this end, quantitative analysis is done based on descriptive and inferential statistical analyses of the 2018 Gran Encuesta Integrada de Hogares, which is a representative survey for Colombia and its 13 more important urban areas. We use the modules on migration, sociodemographic variables of the household and occupation relative to the population aged 14 to 65. Results: Only 24,5% of Venezuelan migrants are affiliated with any health care provider in contrast to 93% of Colombians. The levels of affiliation diminished from 82% among Venezuelans who arrived in 2013 or before to 10% among Venezuelans who arrived in 2017-2018. Venezuelans registered in the health system are a select population in sociodemographic terms; younger, more educated, with more labor participation and higher income than the native population in Colombia. The low insertion of Venezuelan immigrants in jobs with a written contract restricts this enrollment. Conclusions: The Venezuelans in Colombia have a very limited affiliation with the health system. Even though this is a right protected by international and national legal frameworks, Venezuelans encounter economic, political, and social barriers to exercise it in Colombia.